Smart demand side management of low-voltage distribution networks using multi-objective decision making - Shahnia, Farhad; Wishart, M.; Ghosh, A.; Ledwich, G.; Zare, F. (The Institution of Engineering and Technology, 2012)
A novel intelligent online demand side management system is proposed for peak load management in low voltage distribution networks. This method uses low cost controllers with low bandwidth two–way communication installed in costumers’ premises and at distribution transformers to manage the peak load while maximizing customer satisfaction. A multi–objective decision making process is proposed to select the load(s) to be delayed or controlled. The efficacy of the proposed control system is verified by simulations of three different feeder types.